Central Government Transfers and Regional Convergence in Portugal - Marta Ferreira Dias; Ricardo Silva (European Regional Science Association (ERSA), 2004)
Over the last decades, the Portuguese economy exhibited an outstanding growth performance. This period of fast economic growth allowed the country to consistently reduce its income gap with respect to the EU average. In spite of this, regions in Portugal exhibited large differences between each other in terms of GDP per capita. Yet, the Portuguese government did make attempts at regional intervention by means of some policy instruments, namely public transfers to local (and regional) government. How successful these policies have been in terms of achieving their goal is still an open question, especially as far as Portuguese Central Government transfers are concerned. The main purpose of the paper is to evaluate if the system of Central Government transfers has affected the intra-regional Portuguese convergence. We haven't found unquestionable evidence that these policies have been effective at stimulating convergence among Portuguese regions and at improving the overall economies of the poorer regions. Keywords: Regional convergence, Central Government transfers, Regional policy JEL Classification: H71; O18; R58
Keywords: H71; O18; R58; 330; Regional convergence; Central Government transfers; Regional policy